Parents' Role in the Education of Children with Special Needs: A Case Study at SMP SLB Negeri 1 Baubau - Wati, Hikma; Jusu, La; Yahya, Safaruddin (Journal of English Language and Education, 2025)
Parents have an important role in accompanying and guiding children with special needs (ABK), both in academic and social aspects. This study aims to examine the role of parents in supporting ABK education at SMP SLB Negeri 1 Baubau and the factors that support and inhibit their involvement. The method used in this study is a qualitative method. The data sources for this study were parents of students and teachers with the type of research used being field research using a qualitative descriptive approach. Data collection techniques used observation, interviews, and documentation methods. The results of the study showed that parents play a role in providing moral support, maintaining communication with teachers, helping with learning at home, and instilling independence in children. Supporting factors include cooperation between parents and schools, the availability of trained teachers, and family and environmental support. However, there are several inhibiting factors such as limited parental knowledge, high levels of forgetfulness in children, and emotional challenges in educating them. In conclusion, the success of ABK education is highly dependent on the synergy between parents, schools, and the surrounding environment, with emotional support, appropriate learning methods, and an inclusive environment.